Marine Square, Port of Spain - (:unkn) unknown (My University, 2010)
The postcard shows The Union Club which once stood at the south east corner of Abercromby Street and today's Independence Square South. Marine Square was renamed to Independence Square in 1962.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Plazas--Trinidad and Tobago; Pavements--Trinidad and Tobago; Sidewalks--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Architecture--Trinidad and Tobago; Fretwork; Wrought-iron--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Bicycles--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Marine Square (Port of Spain); Independence Square (Port of Spain)